A framework to assess management performance in district health systems: a qualitative and quantitative case study in Iran - Jafar Sadegh Tabrizi; Kamal Gholipour; Shabnam Iezadi; Mostafa Farahbakhsh; Akbar Ghiasi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
The aim was to design a district health management performance framework for Iran's healthcare system. The mixed-method study was conducted between September 2015 and May 2016 in Tabriz, Iran. In this study, the indicators of district health management performance were obtained by analyzing the 45 semi-structured surveys of experts in the public health system. Content validity of performance indicators which were generated in qualitative part were reviewed and confirmed based on content validity index (CVI). Also content validity ratio (CVR) was calculated using data acquired from a survey of 21 experts in quantitative part. The result of this study indicated that, initially, 81 indicators were considered in framework of district health management performance and, at the end, 53 indicators were validated and confirmed. These indicators were classified in 11 categories which include: human resources and organizational creativity, management and leadership, rules and ethics, planning and evaluation, district managing, health resources management and economics, community participation, quality improvement, research in health system, health information management, epidemiology and situation analysis. The designed framework model can be used to assess the district health management and facilitates performance improvement at the district level.